A comparison of three different needles used for spinal anesthesia in terms of squamous epithelial cell transport risk - Cigdem, Unal Kantekin; Sevinc, Sahin; Esef, Bolat; Sureyya, Ozturk; Muzaffer, Gencer; Akif, Demirel (Elsevier Science Inc, 2017)
Background and objectives: To investigate the differences in the number of squamous epithelial cells carried to the spinal canal by three different types of spinal needle tip of the same size. Methods: Patients were allocated into three groups (Group I, Group II, Group III). Spinal anesthesia was administered to Group I (n=50) using a 25G Quincke needle, to Group II (n=50) using a 25G pencil point spinal needle, and to Group III (n=50) using a non-cutting atraumatic needle with special bending. The first and third drops of cerebral spinal fluid (CSF) samples were taken from each patient and each drop was placed on a slide for cytological examination. Nucleated and non-nucleated squamous epithelial cells on the smear preparations were counted. Results: There was statistically significant difference between the groups in respect to the number of squamous epithelial cells in the first drop (p < 0.05). Group III had lower number of squamous epithelial cells in the first drop compared to that of Group I and Group II. Mean while Group I had higher number of squamous epithelial cells in the third drop compared to the other groups. The number of squamous epithelial cells in the first and third drops was statistically similar in each group respectively (p > 0.05 for each group). Conclusions: In this study of different needle tips, it was seen that with atraumatic needle with special bending a significantly smaller number of cells were transported when compared to the Quincke tip needles, and with pencil point needles. (C) 2016 Sociedade Brasileira de Anestesiologia. Published by Elsevier Editora Ltda.
Comparação de três agulhas diferentes usadas para raquianestesia em relação ao risco de transporte de células epiteliais escamosas
Keywords: Spinal anesthesia; Cerebrospinat fluid; Spinal needles; Epithelial cells